Analysis of screen-detected pulmonary nodules before and after the novel coronavirus epidemic: a multicenter retrospective cohort study - He, Zemin; Liu, Keting; Wu, Ling; Wei, Qiang; Shen, Qingwei (Frontiers in Oncology, 2025)
ObjectiveTo analyze the screening results for pulmonary nodules before and after the COVID-19 epidemic to understand the influence of the COVID-19 epidemic on the detection rate of pulmonary nodules and the detection rate of high-risk pulmonary nodules.MethodsA total of 18,906 chest CT scans were performed between March and November 2022 and between March and November 2023. Subjects from March to December 2022 were divided into the pre-epidemic group, and subjects from March to December 2023 were divided into the post-epidemic group. The detection rates of lung nodules, high risk nodules, different age groups, and gender groups were analyzed.ResultsA total of 11513 lung nodules were detected during screening. A total of 841 high risk nodules were detected, and the detection rate of solid nodules was significantly higher in the postepidemic group than in the pre-epidemic group. The detection rate of fibrotic changes was significantly higher in the postepidemic group than in the pre-epidemic group. The detection rate of pulmonary nodules is significantly higher in those aged > 51 years compared to those aged 50 years and below.ConclusionIn the post-COVID-19 period, there has been a significant increase in the detection of solid pulmonary nodules. This increased detection rate is predominantly observed in medical patients over 51 years of age. However, the COVID-19 epidemic has not resulted in an increased detection rate of high risk nodules.